Eksplorasi Keragaman Morfologi dan Karakter Penciri Tanaman Kopi Lokal “Tuni” di Kabupaten Seram Bagian Barat, Maluku - Andi Ardiansyah; Asri Subkhan Mahulette; Abdul Karim Kilkoda (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2026)
West Seram Regency is one of the regions supplying local Tuni coffee in Maluku. Until now, information on the morphological diversity and characteristics of local Tuni coffee in West Seram Regency has not been widely reported. This study aims to analyze the morphological diversity and characteristics of local Tuni coffee plants in West Seram Regency. Morphological characterization was carried out in several distribution locations of local Tuni coffee in West Seram Regency, including: Kairatu Village, Nuruwe Village, Waesamu Village, Tanah Goyang Hamlet, Piru Village, and South Buano Village. Morphological diversity characterization was carried out on 50 samples of local Tuni coffee plants, using the modified